2017
DOI: 10.1083/jcb.201704120
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 regulation of Ncd reveals a new mechanism for targeting proteins to the spindle in oocytes

Abstract: 14-3-3 interacts with the kinesin-14 Ncd and prevents it from binding microtubules. Aurora B provides a spatial cue that releases Ncd from 14-3-3 around chromosomes, allowing Ncd to selectively bind the spindle microtubules in the large volume of oocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 48 publications
6
59
0
Order By: Relevance
“…Such events may be under the control of environmental factors that elicit signaling cascades relevant to KIFC1. KIFC1 can be degraded by a CDK1-dependent event (Singh et al, 2014) or another phosphorylation pathway (Molodtsov et al, 2016;Beaven et al, 2017), either of which could thrust a motile growth cone into a period of stalling or an axon into a bout of retraction. Dendrites might use KIFC1 quite differently from axons given that dendrites contain microtubules of mixed polarity orientation (Baas et al, 1991;Sharp et al, 1995;Lin et al, 2012;Yau et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Such events may be under the control of environmental factors that elicit signaling cascades relevant to KIFC1. KIFC1 can be degraded by a CDK1-dependent event (Singh et al, 2014) or another phosphorylation pathway (Molodtsov et al, 2016;Beaven et al, 2017), either of which could thrust a motile growth cone into a period of stalling or an axon into a bout of retraction. Dendrites might use KIFC1 quite differently from axons given that dendrites contain microtubules of mixed polarity orientation (Baas et al, 1991;Sharp et al, 1995;Lin et al, 2012;Yau et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have suggested that restricting spindle assembly proximal to the chromosomes involves inhibition of spindle assembly factors in the cytoplasm (Beaven et al, 2017;Das et al, 2018;Rome and Ohkura, 2018). For example, the kinesin NCD that has been shown to be inhibited by 14-3-3, which is released by Aurora B phosphorylation (Beaven et al, 2017). We propose that the release of the CPC from the chromosomes locally overrides this inhibition and activates spindle assembly factors.…”
Section: Cpc-dependent Chromosome-directed Spindle Assembly In Oocytmentioning
confidence: 76%
“…Third, and most important, it explains how spindle assembly is restricted to the chromosomes in an acentrosomal system (Ohkura, 2015;Reschen et al, 2012;Rome and Ohkura, 2018); it is based on an HP1-Borealin interaction. We and others have suggested that restricting spindle assembly proximal to the chromosomes involves inhibition of spindle assembly factors in the cytoplasm (Beaven et al, 2017;Das et al, 2018;Rome and Ohkura, 2018). For example, the kinesin NCD that has been shown to be inhibited by 14-3-3, which is released by Aurora B phosphorylation (Beaven et al, 2017).…”
Section: Cpc-dependent Chromosome-directed Spindle Assembly In Oocytmentioning
confidence: 99%
See 1 more Smart Citation
“…cDNAs were then recombined into Gateway destination vectors using LR Clonase II reaction following the manufacturer’s protocol (Invitrogen). To generate transgenic flies expressing a GFP-tagged protein under the UASp promoter, we used φPGW modified from destination vector pPGW of the Murphy’s Gateway collection (https://emb.carnegiescience.edu/drosophila-gateway-vector-collection) by adding the φC31 attB recombination site (Beaven et al, 2017).…”
Section: Methodsmentioning
confidence: 99%